Analysis of AC-DC Converter Circuit Performance With Difference Piezoelectric Transducer Array Connection - Zainal Abidin, Nik Ahmad Kamil; Mohd Nayan, Norkharziana; Ali, Azuwa; Azli, N. A.; Nordin, N. M. (International Journal of Integrated Engineering, 2020)
This research presents a simulation analysis for the AC-DC converter circuit with a different configurations of the array connection of the piezoelectric sensor. The selection of AC-DC converter circuits is full wave bridge rectifier (FWBR), parallel SSHI (P-SSHI) and parallel voltage multiplier (PVM) with array configuration variation in series (S), parallel (P), series-parallel (SP) and parallel-series (PS). The system optimizes with different load configurations ranging from 10 kâ„¦ to 1 Mâ„¦. The best configuration of AC-DC converter with an appropriate array piezoelectric connection producing the optimum output of harvested power is presented. According to the simulation results, the harvested power produced by using P-SSHI converter connected with 3 parallel piezoelectric transducer array was 85.9% higher than for PVM and 15.88% higher than FWBR.